EVALUASI KEBIJAKAN GERAKAN NASIONAL PENINGKATAN PRODUKSI DAN MUTU TANAMAN KAKAO PADA DINAS KEHUTANAN DAN PERKEBUNAN KABUPATEN SIGI - Purwanto, Purwanto (Katalogis, 2016)
This research aims at describing, the evaluation of policy and It’s Development to the Implementation of the National Movement of the Quality of Cacao Plants Improvement at Sigi Regency. This research used a qualitative descriptive method. The data were collected trough observations, interviews, and documentations. This seven informants were taken through purposiv sampling. The resulth show that the Evaluation of Policy and It’s Development to the Implementation of the National Movement of the Quality of Cacao Plants Improvement at Sigi Regency is still not optimal, It mostly influenced by some faktors: 1) effectiveness aspect was still low, 2) efficiency aspect was will low 3) adequacy aspect was low, 4) Equalization aspect was still low, 5) responsiveness aspect was still low 6) Accuracy aspect was good.